2020
DOI: 10.1002/lio2.482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of predictive value of olfactory dysfunction, as a screening tool for COVID‐19

Abstract: Objectives: At the end of 2019, SARS-CoV-2 was identified, the one responsible for the COVID-19 disease. Between a 5.1% and a 98% of COVID-19 patients present some form of alteration in their sense of smell. The objective of this study is to determine the diagnostic yield of the smell dysfunction as screening tool for COVID-19. Methods: Cross-sectional, observational, and pro-elective study was performed in a tertiary care hospital from May 25th to June 30th, 2020. One hundred and thirtynine patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 24 publications
1
33
2
Order By: Relevance
“…Prevalence of GD was reported by 92 studies (59%); the large inter-study variability was confirmed also for this disturbance (range: 0% 81 – 89% 83 ).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Prevalence of GD was reported by 92 studies (59%); the large inter-study variability was confirmed also for this disturbance (range: 0% 81 – 89% 83 ).…”
Section: Resultssupporting
confidence: 52%
“…Finally, we grouped studies based on nationality of the population, with one group comprising studies carried out in the European Union or United States (n=111, 71%), and the other including investigations performed in the rest of the world (n=45, 29%). In the European Union/United States group, prevalence range for OD and GD were 0% 81 - 98% 82 and 0 81 - 89% 83 , respectively; in the rest of the world group, prevalence range for OD and GD were 1% 89 - 89% 90 and 1 89 - 87% 91 , respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Gorzkowski et al, and Romero-Gameros, C.A. et al, reported 11.6 and 10 days, respectively as the mean recovery time from onset of OD (21,23). In the study by Cho et al, mean time for GD recovery was 9.5 ± 6.8 days and the complete recovery rate of GD was 83.3% (32).…”
Section: Discussionmentioning
confidence: 93%
“…In the study of Romero-Gameros, C.A. et al the incidence of OD in women was 63.5% (21). In addition, the study by Chary et al and Gorzkowski et al reported higher incidence of OD in women than in men (22,23).…”
Section: Discussionmentioning
confidence: 93%